In-hospital mortality and 6-months prognosis on cardiogenic shock depending on the aetiology in a Mediterranean cohort. The Shock-CAT Study. (2nd May 2022) - Garcia-Garcia, C; Andrea, R; Sanz, E; Ruiz, M; Aboal, J; Pastor, P; Buera, I; Sionis, A; Lopez, T; Perez-Rodriguez, M; Ariza, A; Tomas, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Mortality in cardiogenic shock (CS) remains very high, although the CS aetiology could influence in the acute-phase and long term prognosis. Purpose: The aim is to investigate in-hospital mortality and 6 months prognosis (all-cause mortality and cardiovascular readmission) in CS patients depending on the CS aetiology in a Mediterranean cohort. Method: Shock CAT study was a multicentre, prospective, observational study conducted between December 2018 and December 2019 in eight public University hospitals in Catalonia (Spain), including CS patients due to acute coronary syndrome (ACS) and other aetiologies. Data on clinical presentation, biomarkers, management, including mechanical assistance support were analyzed comparing ACS and non-ACS patients. In-hospital and 90-days mortality and 6-months prognosis (mortality and cardiovascular readmission) were available and have been compared between groups. Results: A total of 382 CS patients were included, mean age was 65.3 (SD 13.9) years and 75.1% were men. Patient were classified in ACS (n=232, 60.7%) and non-ACS (n=150, 39.3%). In ACS group, 77.6% were STEMI, reperfusion in 84.7% of cases, all with primary angioplasty, 9% developed mechanical complications and 19.4% primary ventricular fibrillation. Main non-ACS aetiologies were severe heart failure (36.2%), malignant arrhythmias (22.1%), valve disease (8.0%) and myocarditis (7.4%). ACS group had less prevalence of women (17.7% vs 36%, p=0.001) and previous myocardial infarction (13.9% vs 24.8%, p=0.007). Mechanical assistance device was implanted more frequently in ACS patients (43.1% vs 16.7%, p<0.001, mainly intraaortic balloon pump (35.6% vs 9.8%, p<0.001) and ECMO (10.7% vs 3%, p=0.01). Both shock risk scores were higher in ACS patients, Cardshock (4.5 vs 4.0, p=0.006) and IABP (2.4 vs 1.9, p=0.005). All-patients in-hospital mortality was 33%. This acute-phase mortality was higher in ACS group (37.1% vs 26.7%, p=0.035) although this difference loss the significance at 90-days (40.9% vs 31.8%, p=0.074) and 6-months (45.2 vs 35.8%, p=0.176). Cardiovascular 6-months readmission was 8.7%, without differences between ACS and non-ACS group (9.7% vs 7.3%, p=0.155, respectively). Conclusions: One-third of cardiogenic shock patients died during hospital admission. Patients with CS due to ACS had 28% higher in-hospital mortality than non-ACS, although this difference decreased at 90 days and 6 months. Cardiovascular 6-months readmission was 8.7%, without differences between groups.